Shedder status—An analysis of self and non-self DNA in multiple handprints deposited by the same individuals over time. (July 2016) - Goray, M.; Fowler, S.; Szkuta, B.; van Oorschot, R.A.H.
Highlights: Shedder status is more reality than myth; consistent differences between individuals noted. Quantity of deposit not influenced by a range of factors. Non-self DNA is usually deposited along with self DNA by handlers of touched objects. Non-self portion is usually, but not always, the minor component. Non-self as a major component is rare and associated with poor shedder depositor. Abstract: There are several studies that suggest that different people deposit different quantities of their own DNA on items they touch, i.e. some are good shedders and others are bad shedders. It is of interest to determine if individuals deposit consistent quantities of their own DNA, no matter the occasion, as well as the degree of variability among individuals. To investigate this, participants were tested for their ability to deposit DNA by placing right and left handprints on separate DNA-free glass plates at three set times during the day (morning, midday and afternoon) on four different days spaced over several weeks. Information regarding recent activities performed by the individual was recorded, along with information on gender, hand dominance and hand size. A total of 240 handprint deposits were collected from 10 individuals and analyzed for differences in DNA quantity and the type of the DNA profile obtained at different times of the day, on different days, between the two hands of the same individual, and between different individuals. Furthermore, the correlation between the deposit quantity and the ratio of self to non-self DNA in the mixed deposits was analyzed to determine if the amount of non-self DNA has an effect on overall DNA quantities obtained. In general, this study has shown that while there is substantial variation in the quantities deposited by individuals on different occasions, some clear trends were evident with some individuals consistently depositing significantly more or less DNA than others. Non-self DNA was usually deposited along with self DNA and, in most instances, was the minor component. Incidents where the non-self portion was the major component were very rare and, when observed, were associated with a poor depositor/shedder. Forensic DNA scientists need to consider the range and variability of DNA a person deposits when touching an object, the likelihood of non-self DNA being co-deposited onto the handled object of interest and the factors that may affect the relative quantity of this component within the deposit.